The Influence of Work Discipline and Organizational Commitment on Employee Performance at the Department of Food Security, Agriculture and Fisheries Service of Majalengka Regency - Amelia Sukmanengsih; Dharliana Hardjowikarto; Juwita Juwita (Green Publisher Indonesia, 2026)
This study was conducted to examine the influence of work discipline and organizational commitment on employee performance at the Food Security, Agriculture, and Fisheries Service of Majalengka Regency (DKP3). The research used an associative quantitative approach with a causal relationship design. The study population consisted of 363 employees, with a sample of 79 respondents selected using the Slovin formula and a simple random sampling technique. The collected data were processed using multiple linear regression analysis with SPSS version 27. The results revealed that, partially, work discipline had a positive and significant influence on employee performance (t-count = 3.512 > t-table = 1.991). Organizational commitment was also proven to have a positive and significant influence on employee performance (t-count = 4.037 > t-table = 1.991) and was more dominant than work discipline. Simultaneously, these two factors significantly affected employee performance, as indicated by an F-count value of 18.074. The coefficient of determination showed that work discipline and organizational commitment accounted for 32.2% of the variance in employee performance, while the remaining variance was influenced by other variables outside the scope of this study.